Pola Pertumbuhan dan Titik Infleksi Sebagai Dasar Memilih Bibit Anjing Kintamani (GROWTH PATTERN AND POINT OF INFLECTION AS THE BASIS OF THE KINTAMANI DOG SELECTION) - SUATHA, I KETUT; Suartini, I Gusti Ayu Agung; Sampurna, I Putu (Jurnal Veteriner; Vol 20 No 2 (2019), 2019)
Kintamani dog growth pattern was observed by measuring the length, circumference and body weight. This study aims to obtain a pattern of growth and determine at what age the growth of kintamani dogs reaches the inflection point (begins to grow slowly) and reaches adult size (begins to stop growing). Data on growth patterns and inflection points of kintamani dogs are useful as a reference for determining the right time for the kintamani dog to be first mated, knowing the existence of abnormalities in growth and nutritional status. The research samples were 90 female kintamani dogs and 90 males aged 0 to 800 days. Measurement of body length and circumference uses a meter, while body weight is measured by digital scales. The growth curve used by the estimator is a sigmoid curve with two parameters: the size of body length, chest circumference and body weight at birth and as an adult. The conclusion of this study is that the pattern of growth in body weight, body length, chest circumference, height of the back limbs and height of the front legs of male and female kintamani dogs has a sigmoid growth pattern. The body size of a female dog has an inflection point or begins to grow slowly and reaches an adult size at a younger age than a male. Female dogs also reach the maximum size earlier than male dogs. The speed of reaching the inflection point on the growth of kintamani dogs were: Chest circumference, front limb height, body length, height of the back leg and body weight. While the speed of achieving adult size were : height of the back leg, body length, height of the front limb, chest circumference and weight.